An Examination of the Factors Influencing the Choice of Route Selection by Intercity Bus Operators in Lagos, Nigeria - Feyisola O, Akinsehinwa; Mobolaji S, Stephens; Chijioke U, Akpudo (Management Analytics and Social Insights, 2025)
The most preferred and highly patronized form of public transportation for regional trips in Nigeria is the intercity bus service. The Origin-Destination (O-D) market operators can serve numerous markets, just as many operators are in the segment. Many O-Ds are served more than others. This study examined the significant factors influencing choice-making by carriers in the selection of O-D markets to serve the movement of passengers away from Lagos to cities in other regions. The study selected five major carriers (operators) based on traffic volume and outputs. They are ABC, GIGM, Chisco, PMT, and YSG Transport, with a total of fifty-five terminals across Lagos State. The terminal operators have the permission of their respective firms to determine which O-Ds to serve. For data gathering, 55 questionnaires were administered to each terminal to solicit answers to questions that would reveal the significant factors in route selection. The factors are demand, fare along routes, political and ethnic affiliation, distance between origin and destination, accruable revenue, monopolistic power, average fuel consumed along routes, labor size required per route, assurance of return passengers or traffic, level of security along the route O-Ds, cost of offering the service, and fuel supply situations for the O-Ds, which serve as the independent variables while the selected routes for the dispatched buses are the dependent variables. Multiple regression analysis was adopted for the study. The outcome of the analysis revealed that choice of route selection by intercity bus operators was influenced by passenger trip demand with a p-value of 0.002182; fare charged (p-value of 0.009264); and political and ethnic affiliation (p-value of 0.027598) in order of significance.